Sistem Penunjang Keputusan Pemilihan Perumahan Terbaik Menggunakan Metode TOPSIS Berbasis GIS - Swastika, Titania Tara; Prastiningtyas, Diah Arifah; Isyriyah, Laila (LPPM STIKI MALANG, 2022)
Real estate agencies are here to help people find their dream home. There are lots of housing with various types of houses. Prospective buyers have a hard time deciding on their dream home, and so do real estate agencies. Housing agencies have difficulty providing housing recommendations according to the wishes of prospective buyers. Housing has many criteria such as location factors, land area, building area, price and others. To help the Housing Agency Team recommend housing with optimal results, a Decision Support System (DSS) is needed, which is an interactive information system that provides information and manipulates data. The appropriate method is the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method used for decision making with many criteria. A view that can make it easier for the Marketing Team to see housing locations requires a map-based application (Geographical Information System). The results of this study are a decision support system for selecting the best housing.